anonymous
  • anonymous
-6x-y=-25 -3x+4y=19 Solve Eacg System By Elimination Steps Only Please
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
LynFran
  • LynFran
mutiple the 2nd equation throughout by 2 to get .equation 3\[-6x+8y=38\]..then take away the 1st and 3rd equatio
anonymous
  • anonymous
you could also multiply the first equation by 4 and then add the 2 equations
anonymous
  • anonymous
Can Someone Show Me The Steps Because I Got The Answer Already

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

LynFran
  • LynFran
\[-6x-y=-25\]\[-(-6x+8y=38)\]
LynFran
  • LynFran
note that the x will cancel leaving \[-9y=-63\]then we can solve for y by dividing both side of the equation by -9
LynFran
  • LynFran
so what will y=?
anonymous
  • anonymous
-72
LynFran
  • LynFran
\[y=\frac{ -63 }{ -9 }\]
anonymous
  • anonymous
Oh So Dont Solve It ?
LynFran
  • LynFran
|dw:1439776842102:dw|
anonymous
  • anonymous
-63/-9=7
LynFran
  • LynFran
correct now since we know that y=7 we can sub y=7 into equation 1 or 2
LynFran
  • LynFran
to find what is x..
anonymous
  • anonymous
Can You Show Me ?
imqwerty
  • imqwerty
-6x-y=-25 - 1equation -3x+4y=19 - 2nd equation Double the second nd subtract from first so as to eleminate x -6x-y - 2(-3x+4y)=-25-2(19) -6x-y+6x-8y=-25-38 -9y=-63 y=-63/-9 y=7 Put this valur of y in any of the two equation s nd get the value of x -6x-y=-25 -6x-7=-25 -6x=-25+7 -6x=-18 x=-18/-6 x=3
LynFran
  • LynFran
using equation 1 |dw:1439777075716:dw|
anonymous
  • anonymous
Thanks You Both :) You Helped !
LynFran
  • LynFran
welcome
imqwerty
  • imqwerty
no prblem :) u r welcome

Looking for something else?

Not the answer you are looking for? Search for more explanations.